Legal review of port management by regional governments from the perspective of regional autonomy - Fathan Ansori; Salamiah Salamiah (Journal of Law Science, 2026)
Port management occupies a strategic position in supporting transportation systems, trade, and regional development, particularly in an archipelagic state such as Indonesia. Nevertheless, the legal regulation of port management still demonstrates the dominance of Central Government authority, which has the potential to weaken the principle of regional autonomy. This article aims to critically analyze the normative disharmony between lex sectoralis in the port sector and lex generalis in regional government law, as well as its implications for the effectiveness of regional autonomy. This study employs a normative legal research method using statutory, conceptual, and comparative approaches. The findings indicate that the legal construction of port management in Indonesia is not yet fully aligned with the principles of decentralization and the development of international practices that position port authorities as relatively autonomous entities. This article recommends the harmonization of regulations and the reformulation of the division of authority in port management in order to strengthen the role of regional governments without neglecting national interests.